2022
DOI: 10.3390/biom12101518
|View full text |Cite
|
Sign up to set email alerts
|

A Promising Candidate in Tendon Healing Events—PDGF-BB

Abstract: Tendon injuries are one of the most common musculoskeletal disorders for which patients seek medical aid, reducing not only the quality of life of the patient but also imposing a significant economic burden on society. The administration of growth factors at the wound site is a feasible solution for enhancing tendon healing. Platelet-derived growth factor-BB (PDGF-BB) has a well-defined safety profile compared to other growth factors and has been approved by the Food and Drug Administration (FDA). The purpose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 85 publications
0
6
0
Order By: Relevance
“…For example, PDGF-AB promotes angiogenesis and reduces infarct size [77]. In a comprehensive review of MSK pathologies, Chen et al summarized the role of PDGF-BB in tendon pathologies; PDGF-BB has a positive effect on tendon healing by enhancing inflammatory responses, promoting angiogenesis, and increasing collagen synthesis and the biomechanics of the repaired tendon [78]. Interestingly, Kovacivic et al showed a dose-dependent response in angiogenesis using different recombinant PDGF-BB doses [79].…”
Section: Platelet-derived Growth Factor-bb (Pdgf-bb)mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, PDGF-AB promotes angiogenesis and reduces infarct size [77]. In a comprehensive review of MSK pathologies, Chen et al summarized the role of PDGF-BB in tendon pathologies; PDGF-BB has a positive effect on tendon healing by enhancing inflammatory responses, promoting angiogenesis, and increasing collagen synthesis and the biomechanics of the repaired tendon [78]. Interestingly, Kovacivic et al showed a dose-dependent response in angiogenesis using different recombinant PDGF-BB doses [79].…”
Section: Platelet-derived Growth Factor-bb (Pdgf-bb)mentioning
confidence: 99%
“…Many in vivo and in vitro studies have shown that different PRP constituents (e.g., platelet growth factors, cytokines, Angs, and various leukocytes) play pivotal effector roles in regulating angiogenesis, matrix formation, and cell proliferation during tissue repair [78]. Bertrand-Duchesne et al studied the mechanisms of various PDGF fractions in PRP that stimulate angiogenesis [125].…”
Section: In Vitro and Animal Studiesmentioning
confidence: 99%
“…Among different strategies, growth factors have been extensively studied to support tendon healing. For example, platelet-derived growth factor-BB (PDGF-BB) is a promising candidate [ 8 ] and has been reported to improve the biomechanical outcome of a fully transected and sutured rabbit Achilles tendon three weeks post-surgery [ 9 ]. Transforming growth factor-β (TGF-β), as a further important growth factor during tendon healing [ 10 ], has been reported to be of favorable influence, particularly when applied at the interface to the bone [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…8−11 For example, lots of researchers analyze the concentration variation of the abnormal expression of PDGF-BB to discriminate the early stage, middle state, and final state of recurrent breast cancer in the growth and progression process. 12 To date, various methods have been explored for PDGF-BB detection, including enzyme-linked immunosorbent assay, 13 fluorescence, 14−17 colorimetry, 18−20 and electrochemical methods. 3 For instance, a fluorescence aptasensor was designed for PDGF-BB detection and extraction by a nanogel.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Platelet-derived growth factor-BB (PDGF-BB), a significant protein biomarker in recognition of tumors, such as colorectal cancer and breast cancer, stimulates the division and proliferation of cancer cells. Recently, numerous studies have demonstrated the close relationship between PDGF-BB and tumor vascular remodeling. For example, lots of researchers analyze the concentration variation of the abnormal expression of PDGF-BB to discriminate the early stage, middle state, and final state of recurrent breast cancer in the growth and progression process . To date, various methods have been explored for PDGF-BB detection, including enzyme-linked immunosorbent assay, fluorescence, colorimetry, and electrochemical methods .…”
Section: Introductionmentioning
confidence: 99%